Teaching nurses teamwork: Integrative review of competency-based team training in nursing education. (September 2018) - Barton, Glenn; Bruce, Anne; Schreiber, Rita
Abstract: Widespread demands for high reliability healthcare teamwork have given rise to many educational initiatives aimed at building team competence. Most effort has focused on interprofessional team training however; Registered Nursing teams comprise the largest human resource delivering direct patient care in hospitals. Nurses also influence many other health team outcomes, yet little is known about the team training curricula they receive, and furthermore what specific factors help translate teamwork competency to nursing practice. The aim of this review is to critically analyse empirical published work reporting on teamwork education interventions in nursing, and identify key educational considerations enabling teamwork competency in this group. CINAHL, Web of Science, Academic Search Complete, and ERIC databases were searched and detailed inclusion-exclusion criteria applied. Studies (n = 19) were selected and evaluated using established qualitative-quantitative appraisal tools and a systematic constant comparative approach. Nursing teamwork knowledge is rooted in High Reliability Teams theory and Crew or Crisis Resource Management sources. Constructivist pedagogy is used to teach, practice, and refine teamwork competency. Nursing teamwork assessment is complex; involving integrated yet individualized determinations of knowledge, skills, and attitudes. Future initiatives need consider frontline leadership, supportive followership and skilled communication emphasis. Collective stakeholder support is required to translate teamwork competency into nursing practice.